Penerapan Matematika Pada Image Processing: Kajian Literatur Dengan Metode Bibliometrik Periode 2013 sampai 2023 - Shobikhah, Anis; Triono, Gaguk; Kurniasari, Norma Devi; Rohman, Trian Basofi (Institut Teknologi Adhi Tama Surabaya, 2023)
ABSTRACTDigital Image Processing is a field of science that studies how to form, process and analyze images to produce information that can be understood by humans. Empirical results show that based on research, poor image quality (image processing) is one of the visible limitations of image processing because it limits efficient data extraction. So it is necessary to study several theories from previous research. This research aims to conduct a bibliometric analysis of journals in Scopus from 2013 to 2023 regarding the application of mathematics in image processing. One of the main objectives is to identify publication trends related to research on the application of mathematics in image processing during the period 2013 - 2023. The results of the research are that China was ranked first, followed by India, Australia, Hong Kong and Singapore. The position of Indonesian researchers is not visible, this indicates that research interest in the topic of image processing and its connection to mathematics is very minimal. This is also a research opportunity to show the novelty of the field of mathematical applications in the field of image processing or related to other information systems. This research emphasizes the importance of modeling and transforming mathematics in sign language by teachers for elementary school level mathematics learning with students with special needs. This also shows that there is a research gap for further research to be carried out by Indonesian researchers.